1999
DOI: 10.1177/00912709922008362
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of Lornoxicam versus Tramadol in Postoperative Pain

Abstract: This randomized double-blind study compared the analgesic efficacy and tolerability of intramuscular lornoxicam and tramadol in 76 patients with moderate to unbearable pain following arthroscopic reconstruction of the anterior cruciate ligament using the patella bone-tendon-bone technique. Patients receiving a single dose of lornoxicam 16 mg experienced significantly greater total pain relief than patients receiving tramadol 100 mg over the following 8 hours. Lornoxicam had greater analgesic efficacy than tram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 14 publications
2
37
0
2
Order By: Relevance
“…However, incidence of side effects was 60% in morphine group and 25% in lornoxicam group (p<0.05). Staunstrup et al [16] investigated the efficacy and tolerability of lornoxicam versus tramadol in postoperative pain. In their study, patients received a single dose of lornoxicam 16 mg and tramadol 100 mg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, incidence of side effects was 60% in morphine group and 25% in lornoxicam group (p<0.05). Staunstrup et al [16] investigated the efficacy and tolerability of lornoxicam versus tramadol in postoperative pain. In their study, patients received a single dose of lornoxicam 16 mg and tramadol 100 mg.…”
Section: Discussionmentioning
confidence: 99%
“…However, the studies showed that lornoxicam does not increase the risk of bleeding in therapeutic dosage. [16][17][18] Krishna et al reported [19] no significant increase in post-tonsillectomy bleeding after NSAID administration. In our study, none of the patients had postoperative bleeding in any group.…”
Section: Discussionmentioning
confidence: 99%
“…4,28 In the postoperative setting, lornoxicam has been well tolerated, with a tolerability profile similar to diclofenac 29 but superior to that of indomethacin. 5 The most frequent adverse effects were dizziness, abdominal pain, headache, and vomiting.…”
Section: Discussionmentioning
confidence: 99%
“…High therapeutic potency is indicated in low doses, with a reduced risk of side eff ects (6)(7)(8). Preliminary research, which requires further confi rmation, suggest that lornoxicam may be a better alternative or adjunctive therapy to opioid analgesics in the treatment of moderate to severe pain (9,10). Studies have also shown that opioids may act in synergy with some NSAIDs, and that such combinations may have therapeutic benefi t in the clinical treatment of infl ammatory pain (11).…”
Section: Research Articlementioning
confidence: 99%